2018
DOI: 10.1074/jbc.ra117.000515
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte integrin Mac-1 (CD11b/CD18, αMβ2, CR3) acts as a functional receptor for platelet factor 4

Abstract: Platelet factor 4 (PF4) is one of the most abundant cationic proteins secreted from α-granules of activated platelets. Based on its structure, PF4 was assigned to the CXC family of chemokines and has been shown to have numerous effects on myeloid leukocytes. However, the receptor for PF4 remains unknown. Here, we demonstrate that PF4 induces leukocyte responses through the integrin Mac-1 (αβ, CD11b/CD18). Human neutrophils, monocytes, U937 monocytic and HEK293 cells expressing Mac-1 strongly adhered to immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 55 publications
7
70
0
Order By: Relevance
“…fLECs and Marco-LECs, both macrophage-rich niches [16], share high expression of Csf1 (Figure 7), and fLECs express Platelet factor 4 ( Pf4 ) (also known as CXCL4) (Figures 4B and S4). CSF-1 and CXCL4 both regulate monocyte and macrophage functions [17; 43] and LEC-derived CSF-1 is required to maintain the LN macrophage niches [17]. As mentioned earlier, Bmp2 is specifically expressed by fLECs (Figures 4B, S4 and S5) that are also enriched for both Smad1 and Smad4 (Figures 4B and S4) suggesting a role for BMP-signaling in fLEC homeostasis.…”
Section: Resultsmentioning
confidence: 85%
“…fLECs and Marco-LECs, both macrophage-rich niches [16], share high expression of Csf1 (Figure 7), and fLECs express Platelet factor 4 ( Pf4 ) (also known as CXCL4) (Figures 4B and S4). CSF-1 and CXCL4 both regulate monocyte and macrophage functions [17; 43] and LEC-derived CSF-1 is required to maintain the LN macrophage niches [17]. As mentioned earlier, Bmp2 is specifically expressed by fLECs (Figures 4B, S4 and S5) that are also enriched for both Smad1 and Smad4 (Figures 4B and S4) suggesting a role for BMP-signaling in fLEC homeostasis.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, β2 integrins enable a cell to adhere to the endothelium, and to extravasate blood vessels at inflamed sites [84]. As mentioned above, of all β2 integrins T cells express only LFA-1 [62], whereas myeloid cells (PMN, monocytes/macrophages and conventional DC) coexpress both LFA-1 and MAC-1 [63,64].…”
Section: Migrationmentioning
confidence: 97%
“…LFA-1 is rather ubiquitously expressed [62], whereas MAC-1 is predominantly apparent on myeloid cells, including PMN, monocytes/macrophages, and conventional dendritic cells (DC) [63]. In addition, it has been reported that MAC-1 is also present on the surface of NK (natural killer) cells and fractions of mast cells, B cells, CD8 + T cells, and CD4 + γδ T cells [64]. In mouse, CD11c/CD18 is rather specifically expressed by all DC populations, and accordingly serves as a well-accepted pan-DC marker [65].…”
Section: Expression Pattern Of β2 Integrinsmentioning
confidence: 99%
“…ITGAM gene encodes the integrin alpha M chain. The alpha M beta 2 integrin is important in the adherence of neutrophils and monocytes to stimulated endothelium, and also in the phagocytosis of complement coated particles and ITGAM as a ligand for the integrin Mac-1 and suggest that many immune-modulating effects previously ascribed to PF4 are mediated through its interaction with Mac-1 [53]. TGFB1I1 encodes a coactivator of the androgen receptor, a transcription factor which is activated by androgen and has a key role in male sexual differentiation.…”
Section: Role Of Candidate Genesmentioning
confidence: 99%